1978
DOI: 10.1056/nejm197812212992501
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Assessment of Amrinone

Abstract: Amrinone, a new bipyridine derivative, exerts a positive inotropic action in experimental preparations and is effective when administered orally to dogs. To assess its immediate effects in man, we studied by cardiac catheterization the hemodynamic responses to amrinone (1.85 to 3.5 mg per kilogram given intravenously) in eight patients with congestive heart failure already receiving full doses of digitalis. the following statistically significant (P less than 0.01) effects were noted: cardiac index increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(77 citation statements)
references
References 2 publications
5
71
0
1
Order By: Relevance
“…Preliminary results in patients (Benotti et al, 1978;Le Jemtel et al, 1979) have confirmed our findings in the dog.…”
Section: Discussionsupporting
confidence: 87%
“…Preliminary results in patients (Benotti et al, 1978;Le Jemtel et al, 1979) have confirmed our findings in the dog.…”
Section: Discussionsupporting
confidence: 87%
“…'F'6 To some extent, this discrepancy can be explained by the influence of cardiac loading conditions on peak positive left ventricular dP/dt. 7 Amrinone, in large doses, produces potent direct arteriolar and venous dilatation that markedly reduces left ventricular filling pressure. This may, therefore, result in a fall in peak positive left ventricular dP/dt that tends to offset the rise produced by the positive inotropic action of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…The study population consisted of 11 consecutive patients with New York Heart Association functional class III or IV congestive heart failure despite optimal standard therapy with digitalis, diuretics, and vasodilators in all cases (table 1). The cause of congestive heart failure was coronary artery disease in six patients and dilated cardiomyopathy in five.…”
Section: Methodsmentioning
confidence: 99%
“…All vasodilators were withheld for at least 36 hr before the time of study, and digitalis and diuretics were withheld on the morning of catheterization. In the cardiac catheterization laboratory, catheters were positioned with patients under local lidocaine (1%) anesthesia as follows: (1) the difference between paired femoral and pulmonary arterial oxygen contents. The following standard formulas were used for derived hemodynamic variables: systemic vascular resistance (SVR, dyne-sec-cnm5) = 79.9 (MP -RA)/CO; pulmonary vascular resistance (PVR, dyne-sec-cmn5) = 79.9 (PA -PCW)/CO; stroke volume index (SVI, ml/beat/M2) = CI/HR: and stroke work index (SWI, g-m/m2) SVI (MP-LVEDP) (0.0136), where MP = mean arterial pressure, RA = mean right atrial pressure, PA = mean pulmonary arterial pressure, PCW = mean pulmonary capillary wedge pressure, LVEDP = left ventricular end-diastolic pressure (all pressures reported in mm Hg), HR = heart rate, CO = cardiac output (liters/min), and CI = cardiac index (liters/min/m2).…”
Section: Methodsmentioning
confidence: 99%